Dielectrophoretic characterization and isolation of jellyfish stinging capsules. Issue 16 (10th July 2017) - Park, Sinwook; Capelin, Daniel; Piriatinskiy, Gadi; Lotan, Tamar; Yossifon, Gilad
Abstract : Jellyfish stinging capsules known as nematocysts are explosive, natural‐injection systems with high potential as a natural drug‐delivery system. These organelles consist of a capsule containing a highly folded thin needle‐like tubule and a matrix highly concentrated with charged constituents that enable the tubule to fire and penetrate a target. For the purpose of using these nematocysts as drug delivery system it is first required to purify subpopulations from heterogeneous population of capsules and to investigate each subpopulation's distinct function and characteristics. Here, the nematocysts' dielectric properties were experimentally investigated using dielectrophoretic and electrorotational spectra with best fits derived from theoretical models. The dielectric characterization adds to our understanding of the nematocysts' structure and function and is necessary for the dielectrophoretic isolation and manipulation of populations. As expected, the effect of monovalent and divalent exchange cations resulted in higher inner conductivity for the NaCl treated capsules; this result stands in agreement with their relative higher osmotic pressure. In addition, an efficient dielectrophoretic isolation of different nematocyst subpopulations was demonstrated, paving the way to an understanding of nematocysts' functional diversity and the development of an efficient drug delivery platform.